The Comparison between SQ5R and Fix–Up Strategy in Reading Comprehension for EFL Secondary Level Learners - Delfia Herwanis; Rahmanita Zakaria; Ari Renaldi; Irna Sari (Journal of Languages and Language Teaching, 2021)
This study investigates the Survey, Question, Read, Recite, Record, Reflect and Review (SQ5R) method and Fix–Up strategy to increase students’ reading comprehension of descriptive texts at Tenth grade of MAN 1 Takengon. The purpose of this research is to find out the comparison of strategies between Survey, Question, Read, Recite, Record, Reflect and Review and Fix–Up strategy. This study used quantitative research using experimental design. The sample of this study consisted of X-A and X-B classes. The X-A Science class was treated as the experimental class, and the X-B class was designed as the control class. Both classes consist of 20 students. The data of this study were attained using observation and reading tests. The results showed that the SQ5R strategy was effective for EFL secondary level learners to facilitate students to attain reading comprehension at the tenth grade of MAN 1 Takengon. This study can be concluded that the SQ5R strategy was more effective than the Fix-Up strategy in teaching reading comprehension classes.